Review on residual stress in selective laser melting additive manufacturing of alloy parts - Fang, Ze-Chen; Wu, Zhi-Lin; Huang, Chen-Guang; Wu, Chen-Wu (Optics and laser technology, 2020)
•The research on residual stress arising in additive manufacturing by SLM are reviewed.•The advantages and disadvantages of mainstream research methods are analyzed.•New concepts on controlling the residual stress in alloy parts by SLM are proposed. The undesirable residual stress accumulated in the parts during the melting and solidification of the metal powder layer by layer retards the further application of the selective laser melting (SLM) process. This paper focuses on reviewing the recent illuminating achievements about physical modeling, experimental characterizing, and active adjusting of the residual stress in the parts fabricated by SLM. The advantages and disadvantages of the mainstream and emerging models or approaches are further analyzed. Based on the status and prospect of the relative techniques, a series of conceptual methods are discussed on mitigating residual stress to make some practical inspiration for developing a systematical residual stress balancing technique for SLM.